2020
DOI: 10.1155/2020/9379756
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Self-Assessed Empathy and Patients’ Perceptions of Physicians’ Empathy: Validation of the Greek Jefferson Scale of Patient Perception of Physician Empathy

Abstract: Aims. This study aims to (i) translate, culturally adapt, and validate the Jefferson Scale of Patient Perception of Physician Empathy questionnaire for the Greek population (Gr-JSPPPE) and (ii) estimate physicians’ self-assessed empathy and patients’ perceptions of physicians’ empathy, investigate their relationship, and assess their predictors. Methods. A total of 189 patients and 17 physicians from an internal medicine clinic took part in the study. A composite questionnaire was administered to the patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 66 publications
0
27
1
5
Order By: Relevance
“…Second to professional characteristics, a high proportion of mostly quantitative studies examined socio-demographic factors. Female gender was associated with higher ECRC in numerous studies 41 , 43 , 45 , 47 , 49 , 52 , 55 , 58 , 61 , 64 , 81 83 , 92 , 94 , 95 , 99 , 101 , 103 , 108 , 113 117 but a comparable number showed no gender effect 39 , 48 , 50 , 51 , 54 , 60 , 72 , 74 , 76 – 80 , 84 , 86 , 96 , 105 , 106 , 116 , 118 121 ; three studies reported males as more compassionate 53 , 111 , 112 . Evidence regarding age was similarly conflicted 39 41 , 43 , 47 , 49 – 51 , 54 , 55 , 58 , 60 , 72 , 77 , 80 , 82 , 84 , 86 , 95 , 99 , 106 ...…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Second to professional characteristics, a high proportion of mostly quantitative studies examined socio-demographic factors. Female gender was associated with higher ECRC in numerous studies 41 , 43 , 45 , 47 , 49 , 52 , 55 , 58 , 61 , 64 , 81 83 , 92 , 94 , 95 , 99 , 101 , 103 , 108 , 113 117 but a comparable number showed no gender effect 39 , 48 , 50 , 51 , 54 , 60 , 72 , 74 , 76 – 80 , 84 , 86 , 96 , 105 , 106 , 116 , 118 121 ; three studies reported males as more compassionate 53 , 111 , 112 . Evidence regarding age was similarly conflicted 39 41 , 43 , 47 , 49 – 51 , 54 , 55 , 58 , 60 , 72 , 77 , 80 , 82 , 84 , 86 , 95 , 99 , 106 ...…”
Section: Resultsmentioning
confidence: 97%
“…Finally, a small number of predominantly qualitative studies showed spirituality 89 , 136 , meaning 136 , and religiosity 137 to predict greater ECRC, although there was no effect of religion 39 . The evidence regarding factors such as living situation 39 , 42 , 72 , 82 , upbringing 98 , 113 , 131 , siblings 64 , 76 , having children 39 , 41 , 49 , 64 , 77 , 111 – 113 , 138 , 139 , the number of children 72 , 82 , 84 , 140 , and marital status 43 , 47 , 49 , 50 , 63 , 64 , 72 , 76 , 77 , 83 , 84 , 86 was conflicted and, hence, inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies can explore the efficacy of various elements of rehearsal simulations objectively using standardized empathy and communication assessment tools and parental feedback, [40][41][42] and can be expanded beyond the NICU context. Using standardized patients trained in displaying realistic emotional reactions instead of NICU colleagues known to the trainee would add realism to the simulation, which was a limitation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…First, only 3 male surgeons with clinical experience as a specialist of 1.5 to 6 years participated in this study, which may limit generalizability. Studies show that women clinicians are more participatory in terms of empathy and information sharing (33,34). It can also be argued that more experienced clinicians might be better at reading patient signals, using strategies to increase patient participation, and detecting signals from the patient that they have not understood the information.…”
Section: Discussionmentioning
confidence: 99%